2022
DOI: 10.1039/d1lc01019k
|View full text |Cite
|
Sign up to set email alerts
|

Desktop-level small automatic guided vehicle driven by a liquid metal droplet

Abstract: Gallium-based liquid metal (LM) is a new type of intelligent material, and its ability to move under the action of an electric field provides new opportunities for the design of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The electrocapillary effect refers to the change in interfacial tension at the liquid-liquid interface caused by an electric field. 20 The motion and deformation of room-temperature liquid metals are typical examples of applications of the electrocapillary effect, [21][22][23][24][25][26][27][28] playing a crucial role in the control of a small amount of liquid. Yun et al 29 reported a small-scale pump designed based on the electrocapillary effect, which utilized the reciprocating motion of a mercury droplet under an electric field to alternately open the inlet and outlet chambers, achieving the directed transport of a small amount of liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The electrocapillary effect refers to the change in interfacial tension at the liquid-liquid interface caused by an electric field. 20 The motion and deformation of room-temperature liquid metals are typical examples of applications of the electrocapillary effect, [21][22][23][24][25][26][27][28] playing a crucial role in the control of a small amount of liquid. Yun et al 29 reported a small-scale pump designed based on the electrocapillary effect, which utilized the reciprocating motion of a mercury droplet under an electric field to alternately open the inlet and outlet chambers, achieving the directed transport of a small amount of liquid.…”
Section: Introductionmentioning
confidence: 99%
“…9 Electrical control of LM droplets has enabled applications such as drug loading and release, 10 pumping fluids in microfluidic devices, 11,12 and driving robotic vehicles. [13][14][15][16] Ga-based LM droplets also possess great interest in many other areas such as three-dimensional (3D) printing, 17 thermal management, 18 flexible electronics, [19][20][21] nanomedicine, [22][23][24] and energy. 25,26 In particular, LM droplets can be used to build actuators.…”
Section: Introductionmentioning
confidence: 99%
“…2 Gallium-based liquid metal (LM) is a kind of liquid alloy material that is similar to mercury but has extremely low toxicity. Via adjustment of the applied external physical field, this controllable liquid metal droplet (LMD) provides new solutions and opportunities for many disciplines and research directions, [3][4][5] especially in the fields of flexible electronics, [6][7][8] microfluidics, [9][10][11][12] soft sensors, 13-15 actuators, [16][17][18][19] micro-robotics, [20][21][22][23][24] and biomaterials. [25][26][27][28] Among them, the liquid metal motor (LMM) is a novel driving concept that presents obvious flexible advantages compared to traditional small motors, such as infinitely variable speed without a transmission chain, noiseless operation, a simple structure, and easy maintenance.…”
Section: Introductionmentioning
confidence: 99%